(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to determine the clinical and paraclinical characteristics of patients with metacarpal and phalangeal fractures treated by surgical fixation at Hue University of Medicine and Pharmacy Hospital, and to evaluate the effectiveness of postoperative care following metacarpal and phalangeal fracture fixation. Subjects and methods: A prospective descriptive case series study was conducted on 41 patients with metacarpal and phalangeal fractures who underwent surgical fixation at Hue University of Medicine and Pharmacy Hospital from September 2023 to January 2024. Study participants were interviewed to collect personal characteristics, combined with wound observation and data extracted from medical records. Results: The mean age of patients was 39.7 ± 15.4 years, with males accounting for 75.6%. Metacarpal fractures accounted for 56.1% of cases, most commonly involving the V metacarpal and the V finger. Seven days after surgery, wounds were dry with mild residual pain; primary wound healing was observed without complications such as bleeding or surgical site infection. The proportion of patients achieving moderate to good recovery outcomes was 95.1%. Conclusion: Postoperative wound care for metacarpal and phalangeal fractures demonstrated favorable outcomes.